Aesthetic of Bedhaya Kidung Gayatri Dance Performance - Wahyu Indriya Laksmi; Pamenang, Nandhang Wisnu; Slamet , Slamet (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2025)
Bedhaya Kidung Gayatri Dance is a dance work created by Dwi Rahmani and directed by Didik Bambang Wahyudi in 2019. This research aims to provide information and references about the aesthetics of the performance form of Bedhaya Kidung Gayatri Dance in terms of the elements of wiraga, wirama, and wirasa addressed to a dancer. The method used in this research is to use qualitative research methods and descriptive and aesthetic approaches. The techniques used in data collection are observation, literature study, interviews, and document utilization. The results of the research can be concluded that the aesthetics of the performance form of Bedhaya Kidung Gayatri Dance can not only be seen from the visualization of motion and musical accompaniment, but also can be viewed from the elements contained in dance, wiraga, wirama, and wirasa.